On the transport and modeling of dispersed oil under ice. (October 2018) - Boufadel, Michel C.; Cui, Fangda; Katz, Joseph; Nedwed, Tim; Lee, Kenneth
Abstract: Theoretical arguments and numerical investigations were conducted to understand the transport of oil droplets under ice. It was found that the boundary layer (BL) in the water under ice produces a downward velocity that reaches up to 0.2% of horizontal current speed, and is, in general, larger than the rise velocity of 70 μm oil droplets. The eddy diffusivity was found to increase with depth and to decrease gradually afterward. Neglecting the gradient of eddy diffusivity when conducting Lagrangian transport of oil droplets would result in an unphysical spatial distribution. When the downward velocity of water was neglected, oil accumulated at the water-ice interface regardless of the attachment efficiency. The lift force was found to scrape off droplets of the ice, especially for droplets ≤ 70 μm. These findings suggest that previous oil spill simulations may have overestimated the number of small droplets (≤70 μm) at the water-ice interface. Highlights: A downward water velocity occurs under the ice due to boundary layer (BL) hydrodynamics. The gradient of eddy diffusivity needs to be considered in Lagrangian oil spill models. Lift at the ice-water interface could scrape off oil droplets of the ice. The findings suggest existing approaches overestimate the amount of small oil droplet (< 70 μm) at the water-ice interface.